A educação da mulher em Lima Barreto - Silva, Jomar Ricardo da (2007)
Lima Barreto has built an educational conception of women in his fictional productions despite nuances inciting scholars to debate his writings and label him as misogynist and philogynist. Thus, the objective of this study is to comprehend, through signs present in his literary works, how women used to be educated in early twentieth century to accomplish the historical differences in gender relations. The main reason for this extract is the periodicity of his publications that started in 1900 by means of chronicles in newspapers and ended in 1922 after his death. For this, we identified codes and rules forged in the social processes to be assimilated by children through diverse institutions, aiming to incite the production of behaviors and social practices represented by the existence men and women in an ever changing society. Gender relations are analyzed within a society for their configuration concept by Nobert Elias (1970) as interdependence bonds among individuals. An investigative method proposed by Ginzburg (1989) was the most adequate to conduct the research on the work of Lima Barreto because it enables us to reconstruct the education concept for women. The dramas and novels analyzed point out the construction of categories such as women education, family, love and seduction revealing the engagement of Lima Barreto with the social problems of the period investigated. It was concluded that gender differentiation has come from family education which kept men and women in opposing sides giving them a marriage perspective that, after consummated, would bring frustration to women causing them to adopt confronting practices against domination strategies through celibacy or adultery. This research constitutes a reflection based on determined representations like justice, respect and duties that were the ideas defended by Lima Barreto in his writings, concerning both broader situations in social life and particular gender relations